Time course of symptomatic orthostatic hypotension and urinary incontinence in patients with postmortem confirmed parkinsonian syndromes: a clinicopathological study. Issue 5 (1st November 1999) - Wenning, Gregor K; Scherfler, Christoph; Granata, Roberta; Bösch, Sylvia; Verny, Marc; Chaudhuri, K Ray; Jellinger, Kurt; Poewe, Werner; Litvan, Irene
Abstract : OBJECTIVE: Although both orthostatic hypotension and urinary incontinence have been reported in a number of parkinsonian syndromes, such as Parkinson's disease (PD), multiple system atrophy (MSA), dementia with Lewy bodies (DLB), corticobasal degeneration (CBD), and progressive supranuclear palsy (PSP), differences in the evolution of these features have not been studied systematically in pathologically confirmed cases. METHODS: 77 cases with pathologically confirmed parkinsonian syndromes (PD, n=11; MSA, n=15; DLB, n=14; CBD, n=13; PSP, n=24), collected up to 1994, formed the basis for a multicentre clinicopathological study organised by the NINDS to improve the differential diagnosis of parkinsonian disorders. The present study determined the time course—that is, latency to onset and duration from onset to death, of symptomatic orthostatic hypotension, and urinary incontinence in the NINDS series. Furthermore, the diagnostic validity of a predefined latency to onset within 1 year of disease onset of symptomatic orthostatic hypotension or urinary incontinence was analysed. RESULTS: Significant group differences for latency, but not duration, of symptomatic orthostatic hypotension and urinary incontinence were found. Latencies to onset of either feature were short in patients with MSA, intermediate in patients with DLB, CBD, and PSP, and long in those with PD. Symptomatic orthostatic hypotension occurring within the first year after disease onset predicted MSA in 75% of cases; early urinary incontinence was less predictive for MSA (56%). CONCLUSION: Latency to onset, but not duration, of symptomatic orthostatic hypotension or urinary incontinence differentiates PD from other parkinsonian syndromes, particularly MSA.